Effect of Electronegativity and Charge Balance on the Visible-Light-Responsive Photocatalytic Activity of Nonmetal Doped Anatase TiO2 - Jibao Lu; Hao Jin; Ying Dai; Kesong Yang; Baibiao Huang (International Journal of Photoenergy)
The origin of visible light absorption and photocatalytic activity of nonmetal doped anatase TiO2 were investigated in details in this work based on density functional theory calculations. Our results indicate that the electronegativity is of great significance in the band structures, which determines the relative positions of impurity states induced by the doping species, and further influences the optical absorption and photocatalytic activities of doped TiO2. The effect of charge balance on the electronic structure was also discussed, and it was found that the charge-balance structures may be more efficient for visible light photocatalytic activities. In addition, the edge positions of conduction band and valence band, which determine the ability of a semiconductor to transfer photoexcited electrons to species adsorbed on its surface, were predicted as well. The results may provide a reference to further experimental studies.